Akhlak and Academic Ethics: Idealism Among Pragmatism in Community Social Life - Nahar, Syamsu; Budianti, Yusnaili; Safitri Ro, Qoriah Elfi Lina (International Journal for Educational and Vocational Studies, 2020)
Basically, in social life in achieving progress it is indicated that a person is able to meet the needs of a social group so that that person can contribute to society. Regardless of the intention of a person, one of the efforts made by the community to obtain education is to get a scholarship so that it gets recognition from the community about their social status. If we look at it in today's society, it seems that this view has started to shift because if we see that the award is more to a degree than from one's knowledge. This has prompted some people to take academic degrees with a path that is not in accordance with the procedure. The procedure that was followed was what damaged the social order and academic ethics. It can be said that this degree was obtained based on the objective, namely degree fever. The academic world is a forum whose process always follows academic ethics through scientific activities. Thus academic ethics is essentially a scientific activity that takes place in higher education which includes universal and developing activities. Higher education institutions must be prepared to accept criticism with mutual respect and not engage in discriminatory activities. Violations committed in academic ethics are something that damages and tarnishes the world of education. In order for these educational values to be implemented optimally, we need a rule that can control the process of implementing education; this is what is called academic ethics. The emphasis on the value of honesty in academic ethics consists of two things, namely in writing scientific papers and completing studies. Therefore, it is demanded that every education actor is systematic and comprehensive and requires commitment from various parties to fix problems in education.